2008
DOI: 10.1021/mp700114j
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Metabolizing Enzyme and Transporter Expression in a Mouse Model of Diabetes and Obesity

Abstract: Obesity and type II diabetes pose a serious human health risk. Obese or diabetic patients usually take prescription drugs that require hepatic and renal metabolism and transport, and these patients sometimes display different pharmacokinetics of these drugs. Therefore, mRNA and protein expression of drug-metabolizing enzymes (DMEs) and transporters was measured in livers and kidneys of adult wild-type and ob/ob mice, which model obesity and diabetes. mRNA expression of numerous DMEs increased by at least 2-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
91
3

Year Published

2011
2011
2012
2012

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 67 publications
16
91
3
Order By: Relevance
“…A notable difference in the data presented in this study compared with the results of Cheng et al (2008) is the lack of alterations observed in kidney transporter expression in DIO mice. Cheng et al (2008) reported multiple changes in renal expression of slco1a1 and abcc4 transporters in kidneys of ob/ob mice.…”
Section: Transporter Expression In Dio Micecontrasting
confidence: 81%
See 3 more Smart Citations
“…A notable difference in the data presented in this study compared with the results of Cheng et al (2008) is the lack of alterations observed in kidney transporter expression in DIO mice. Cheng et al (2008) reported multiple changes in renal expression of slco1a1 and abcc4 transporters in kidneys of ob/ob mice.…”
Section: Transporter Expression In Dio Micecontrasting
confidence: 81%
“…Transporter expression in ob/ob mice has been described previously (Cheng et al, 2008). ob/ob mice, in general, exhibited decreased uptake of transporter and increased efflux of transporter expression in liver compared with that in C57BL/6 mice (Cheng et al, 2008).…”
Section: Downloaded Frommentioning
confidence: 74%
See 2 more Smart Citations
“…Another study also showed that the hepatic expression of uptake transporters (Oatp1a1, 1a4, 1b2, 1a6, 2b1, and Ntcp) in diabetic mice decreased significantly compared to the wild type controls (Cheng et al, 2008). Our recent study showed no effect of high fat in DIO mice on gene expression of hepatic transporters (Mrp2 and 3, and Mdr1b) (Ghose et al, 2011b).…”
Section: Drug Transportersmentioning
confidence: 80%